Perbedaan Berpikir Kritis Siswa Antara yang Menggunakan Model Inquiry Based Learning dengan Model Problem Based Learning Ditinjau dari Gaya Kognitif Reflektif Dan Impulsif - Nur Farida; Imas Cintamulya (Universitas Sebelas Maret, 2018)
One of the higher-order thinking skills that is competence in curriculum 2013 is critical thinking skills. However, in the actual learning process the teacher has not yet empowered the students' critical thinking skills. In addition, other aspects such as cognitive styles have also not been considered. This study aims to examine students' critical thinking differences in terms of reflective and impulsive cognitive styles between those using Inquiry Based Learning model with Problem Based Learning model. The research method used is Quasi experiment that is in experiment class I using Inquiry Based Learning model and experiment class II using Problem Based Learning model. The study sample were 64 students of VII B class and VII C class of SMP Negeri 7 Tuban consist of 22 reflective students and 19 impulsive students. To obtain reflective and impulse cognitive style data is used Matching Familiar Figure Test (MFFT). The students' critical thinking data in the two experimental classes as a whole was analyzed using the Independent Samples Test or t-test. While the critical thinking data reflective and impulsive students were analyzed using Mann-Whitney test. The results showed that there is no difference ofcritical thinking between students using Inquiry Based Learning model with Problem Based Learning model. Both are equally able to empower students' critical thinking. However, if examined further by cognitive style, there is a difference between the two experimental classes. Model Inquiry Based Learning is better, because critical thinking reflective students with impulsive students.